PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN ACEH TIMUR - M Zubir (AL-ILMU, 2022)
This study aims to determine the effect of work discipline on the performance of the education office staff of the East Aceh district. By using descriptive quantitative research methods. Data collection techniques using observation, questionnaires, and documentation. The data analysis technique used inferential statistical analysis. The results showed that work discipline at the East Aceh district education office had a significant influence on employee performance, this was evidenced from the results of data analysis, namely the level of work discipline was in the good category. Supported by 4 variable indicators, namely obeying the rules of time, obeying organizational rules, obeying behavior at work, obeying other organizational rules. The level of employee performance is in the good category. Supported by 5 variable indicators, namely quality of work, punctuality, initiative, ability, communication. The results of the analysis and hypothesis testing indicate that there is a positive and significant influence between work discipline and employee performance.